Plasma Cell-Free DNA and Caspase-3 Levels in Patients with Chronic Kidney Disease - Clementi, Anna; Virzì, Grazia Maria; Manani, Sabrina Milan; de Cal, Massimo; Battaglia, Giovanni Giorgio; Ronco, Claudio; Zanella, Monica (Journal of clinical medicine, 2023)
Background: Cell-free plasma DNA (cfDNA) is circulating extracellular DNA arising from cell death mechanisms (apoptosis, necrosis, etc.). It is commonly existent in healthy individuals, but its ranks increase in diverse clinical circumstances, such as kidney disease, sepsis, myocardial infarction, trauma and cancer. In patients with advanced chronic kidney disease, cfDNA is connected to inflammation, and it has been associated with higher mortality. Caspase-3 plays a dominant role in apoptosis, a mechanism of programmed cell death involved in the pathogenesis and progression of chronic kidney disease (CKD). The aim of this pilot study was the evaluation of cfDNA levels and caspase-3 concentrations in patients with chronic kidney disease, in order to investigate the potential role of these molecules, deriving from inflammatory and apoptotic mechanisms, in the progression of renal damage. Methods: We compared cfDNA and caspase-3 levels in 25 CKD patients and in 10 healthy subjects, evaluating their levels based on CKD stage. We also explored correlations between cfDNA and caspase-3 levels in CKD patients and between cfDNA and caspase-3 levels and serum creatinine and urea in this population. Results: We observed that cfDNA and caspase-3 levels were higher in patients with CKD compared to healthy subjects, in particular in patients with advanced renal disease (CKD stage 5). A positive correlation between cfDNA and caspase-3 levels and between cfDNA and caspase-3 and creatinine and urea were also noticed. Conclusions: Patients with chronic kidney disease show higher levels of cfDNA and caspase-3 levels compared to the control group. Based on these preliminary results, we speculated that the worsening of renal damage and the increase in uremic toxin concentration could be associated with higher levels of cfDNA and caspase-3 levels, thus reflecting the potential role of inflammation and apoptosis in the progression of CKD. Future studies should focus on the validation of these promising preliminary results.